2001
DOI: 10.1258/0956462011923165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-term adherence on virological and immunological success of HAART: a case study among French HIV-infected IDUs

Abstract: To evaluate the impact of injection drug users (IDUs) adherence on effectiveness of highly active antiretroviral therapy (HAART), repeated measures of plasma viral load and CD4+ counts before HAART initiation and at last visit in the cohort were studied. Data were collected by means of patient's face-to-face and self-administered questionnaires about adherence to HAART during the week prior to the last visit. Of a total of 119 patients treated with HAART, undetectable viral load was obtained for 55 patients (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Eleven studies defined optimal antiretroviral adherence as 100% uptake of the prescribed doses (Crisp et al 2004;Haug et al 2005;Martin et al 2005;Palepu et al 2003aPalepu et al , b, 2004bPradier et al 2001;Purcell et al 2004;Sharpe et al 2004;Waldrop-Valverde and Valverde 2005;WaldropValverde et al 2006). Eight studies assessed optimal adherence as greater than 95% (Escobar et al 2003;Kerr et al 2004;Knowlton et al 2006;Palepu et al 2004bPalepu et al , 2006Turner et al 2003;Wood et al 2003bWood et al , 2004b.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies defined optimal antiretroviral adherence as 100% uptake of the prescribed doses (Crisp et al 2004;Haug et al 2005;Martin et al 2005;Palepu et al 2003aPalepu et al , b, 2004bPradier et al 2001;Purcell et al 2004;Sharpe et al 2004;Waldrop-Valverde and Valverde 2005;WaldropValverde et al 2006). Eight studies assessed optimal adherence as greater than 95% (Escobar et al 2003;Kerr et al 2004;Knowlton et al 2006;Palepu et al 2004bPalepu et al , 2006Turner et al 2003;Wood et al 2003bWood et al , 2004b.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eighteen of the 38 studies evaluated HAART-related clinical outcomes (Avants et al 2001;Bouhnik et al 2005;Carrieri et al 2003a;Duran et al 2001;Knowlton et al 2006;Lucas et al 2001;McNabb et al 2001;Moatti et al 2000;Palepu et al 2003aPalepu et al , b, 2004aPalepu et al , b, 2006Pradier et al 2001;Roca et al 1999;Waldrop-Valverde et al 2006;Wood et al 2003aWood et al , 2004b (Table 3).…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…For the fortunate 20% of those in need worldwide for whom it is available [2], HAART has dramatically reduced viral load; improved immunologic status, physical health, and quality of life; and contributed to substantial declines in HIV-related morbidity and mortality (eg, [3][4][5][6][7][8]). …”
Section: Introductionmentioning
confidence: 99%
“…Although antiretroviral treatments (i.e., highly active antiretroviral treatment, HAART) have greatly improved the outlook of HIV disease, strict medication adherence is necessary for HAART therapy to be effective in slowing disease progression. Even low levels of nonadherence can dramatically impact HAART's effectiveness (Bangsberg et al, 2000;Knobel et al, 2001;Low-Beer et al, 2000;Paterson et al, 2000;Pradier et al, 2001;Sethi et al, 2003). Paterson et al (2000) reported a significant increase in relative risk for virologic failure in patients adhering to less than 95% of their regimen.…”
Section: Introductionmentioning
confidence: 99%